THE INFLUENCE OF ECONOMIC VALUE ADDED, GOING CONCERN OPINION AND DIVIDEND POLICY ON STOCK PRICES IS MEASURED BY MARKET VALUE ADDED - Anastasia Awa; Endang Ruhiyat; Sugiyanto (ZILLZELL MEDIA PRIMA, 2024)
This study aims to examine the influence of Economic Value Added, Going Concern Opinion and Dividend Policy on Stock Prices as analyzed by Market Value Added. This type of research is associative quantitative research. The type of data used is secondary data obtained from the company's www.idx.co.id and website. The population in this study is manufacturing companies in the consumer non-cyclicals sector that have been listed on the IDX for the 2018-2022 period. The determination of the sample used the purposive sampling method, the number of research samples was 29 companies, with a research year of 5 years, the total data in this study was 145 data and the data was tested using the help of EViews software version 12. The data analysis technique used is panel data model regression. Based on the results of this study, the Economic Value Added variable has a positive effect on the Stock Price, the Going Concern Opinion has no effect on the Stock Price, the Dividend Policy has no effect on the Stock Price, the Market Value Added cannot decode the relationship between the Economic Value Added and the Stock Price, the Market Value Added cannot decode the relationship of Going Concern Opinion to Stock Price, Market Value Added cannot decode the relationship of Dividend Policy to Stock Price.